Proteomic Responses of Dark-Adapted Euglena gracilis and Bleached Mutant Against Light Stimuli - Chen, Zhenfan; Chen, Zixi; Zhu, Jiayi; He, Jiayi; Liu, Qiong; Zhu, Hui; Lei, Anping; Wang, Jiangxin (Frontiers in Bioengineering and Biotechnology, 2022)
Euglena gracilis has secondary endosymbiotic chloroplasts deriving from ancient green algae. Its chloroplasts are easily lost under numerous conditions to become permanently bleached mutants. Green cells adapted in the dark contain undeveloped proplastids and they will be developed into mature chloroplasts after light exposure in 3 days. Thus, E. gracilis is one of the ideal model species for chloroplast development study. Previous studies about chloroplast development in E. gracilis majorly focused on morphology, physiology, whereas few studies have addressed the regulatory processes induced by light in the proteome. In this study, the whole-genome proteome of dark-adapted E. gracilis (WT) and permanently ofloxacin-bleached mutant (B2) was compared under the light exposure after 0 h, 12 h, and 72h. Surprisingly, the photosynthesis-related proteins were up-regulated over time in both WT and B2. The losing functional chloroplasts B2 seemed to possess a complete photosynthetic function system. Both WT and B2 exhibited significant light responses with similar alternation patterns, suggesting the sensitive responses to light in proteomic levels. This study confirmed light-induced chloroplast development in WT from dark, and also for the first time investigate the light responses of B2, providing more information about the unknown functions of residual plastids in bleached mutants.